Glycoprotein non-metastatic melanoma protein B expression correlates with the prognosis of acute liver injury/failure - Kumagai, Kotaro; Kanmura, Shuji; Mawatari, Seiichi; Nakamura, Yuko; Eguchi, Hiromi; Taniyama, Oki; Toyodome, Ai; Ijuin, Sho; Sakae, Haruka; Tabu, Kazuaki; Oda, Kohei; Shimata, Keita; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Glycoprotein non-metastatic melanoma protein B (GPNMB) is expressed in macrophages during recovery from acute liver injury (ALI) in carbon tetrachloride (CCl4)-induced liver injury model mice. In this retrospective study, we assessed whether GPNMB levels in the serum and injured liver correlate with liver injury severity and prognosis in patients with ALI or acute liver failure (ALF).The study involved 56 patients with ALI or ALF who visited the Kagoshima University Hospital. Serum GPNMB level was measured over time, and the localization, proportion, origin, and phenotype of GPNMB-expressing cells in the injured liver were assessed. Finally, the phenotypes of human monocyte-derived macrophages and peripheral blood mononuclear cells (PBMCs) of patients with ALI and ALF were analyzed.Results: Peak GPNMB levels were significantly higher in patients with ALF and hepatic encephalopathy (HE), as well as in those who underwent liver transplantation or died, than in others. The peak GPNMB level correlated with prothrombin activity, prothrombin time-international normalized ratio, Model for End-stage Liver Disease score, and serum hepatocyte growth factor level. GPNMB was expressed in CD68-positive macrophages, and its level increased with the severity of liver injury. The macrophages showed the same polarization as M2c macrophages induced with interleukin-10 from human monocytes. Moreover, PBMCs from patients with ALF exhibited an immunosuppressive phenotype.We found that GPNMB levels in the serum and injured liver, which increased in patients with ALF, especially in those with HE, correlated with the severity of liver injury and prognosis of ALI and ALF. Moreover, GPNMB-positive macrophages exhibited the M2c phenotype.2 This is a provisional file, not the final typeset article Our results indicate that persistently high GPNMB levels may be a prognostic marker in patients with ALI and ALF.